1987
DOI: 10.1111/j.1600-0609.1987.tb00769.x
|View full text |Cite
|
Sign up to set email alerts
|

Impaired heme synthesis in a family with Pelger‐Huët anomaly, recurrent abdominal pain attacks and impaired neutrophil motility in vitro

Abstract: Heme synthesis was studied by measuring the activity of δ‐aminolevulinic acid synthase (AmLev synthase) in granulocytes, the activity of δ‐aminolevulinic acid dehydratase (AmLev dehydratase) and of uroporphyrinogen I synthase in erythrocytes as well as the concentrations of coproporphyrin and protoporphyrin in erythrocytes of 6 patients with Pelger‐Huët anomaly. 3 of these patients from the same kindred had a syndrome of recurrent attacks of fever and abdominal pains, a tendency to skin infections, delayed wou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The index family has been studied since the 1970s. [16][17][18] A systems-level approach combining genomics, transcriptomics, and proteomics finally made it possible to unravel the causative pathogenic mechanisms. In conclusion, CAIN reveals GOF mechanisms resulting in autoinflammation and immunodeficiency, which are potentially relevant for various transcription factor-related diseases.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The index family has been studied since the 1970s. [16][17][18] A systems-level approach combining genomics, transcriptomics, and proteomics finally made it possible to unravel the causative pathogenic mechanisms. In conclusion, CAIN reveals GOF mechanisms resulting in autoinflammation and immunodeficiency, which are potentially relevant for various transcription factor-related diseases.…”
Section: Discussionmentioning
confidence: 99%
“…14 Early studies in Cebpe knockout mice showed Cebpe to be integral for maintenance of constitutive levels of several cytokines, including IFN-g. 15 We report an autosomal recessive GOF PID, C/EBPε-associated autoinflammation and immune impairment of neutrophils (CAIN), in a family with a genetically uncharacterized autoinflammatory syndrome. [16][17][18] According to our results, C/EBPε acts as a regulator of both the inflammasome and interferome. Homozygous missense mutations in CEBPE (14:23586886 C->T;p.Arg219His) resulted in markedly decreased C/EBPε association with transcriptional repressors and increased occupancy on chromatin, leading to dysregulated C/EBPε-mediated transcription of interleukin and interferon response genes in neutrophils.…”
mentioning
confidence: 90%
See 2 more Smart Citations